An Analysis of Students’ Difficulties In Listening Comprehension at English Education Department in Faculty of Teacher Training And Education of Universitas Ekasakti - Yessy Marzona (Jurnal Ilmiah Pendidikan Scholastic, 2023)
Listening is part of the English language skills component which is quite complex in EFL (English as Foreign Language) learning practices. Difficulties in this skill is experienced by students in the Indonesian context consisting of various ethnicities, languages and cultures. Listening skill would enable people to improve their ability in communication. However, in some cases of EFL classes, college students still find difficulties in learning this skill since it needs more attentions and concentrations in order to comprehend the language materials. This study tries to discover the listening difficulties encountered by English Education Department students of faculty of teacher training and education in Universitas Ekasakti while taking the listening courses. The design of this research was descriptive research with population were the second-year students who have taken the Listening comprehension. They were 17 members . The researcher used total sampling technique to take the sample so all population was sample. The instrument used was listening comprehension test. The results of the study showed that there are four main categories of students’ difficulties in listening, namely: difficulties related to the learning materials (unfamiliar topics, topic that doesn’t exist in students’ cultures, too many unfamiliar words, and the length of the spoken texts); difficulties related to the speakers (unclear pronunciation, varieties of accents, and the speed of speaking); difficulties related to the listeners (inferring the meanings of unknown words, losing concentration, memory, and the length of the questions); and difficulties related to the physical settings (noises around, the online learning media used, and the internet connection).